2022
DOI: 10.4039/tce.2022.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different diet on the survivorship, life cycle, and fecundity of eri silkworm Samia cynthia ricini Boisduval (Lepidoptera: Saturniidae)

Ihsan Nurkomar,
Dina Wahyu Trisnawati,
Muhammad Humam Tedy

Abstract: Cassava (Euphorbiaceae), castor (Euphorbiaceae), and tropical almond (Combretaceae) have been suggested as three different possible natural diet sources for Samia cynthia ricini (Drury, 1773) (Lepidoptera: Saturniidae), a species of silkworm that is reared in Indonesia because it is able to produce good-quality silk. This research aims to study the effect of the types of diet on the survivorship, development time, and fecundity of S. c. ricini. The research was conducted by giving the three types of diet to S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…In this study, R. communis was a better host plant than A. excelsa , as S. ricini larvae fed on the Scr diet displayed significantly higher ( p ≤ 0.05) larval weight gain, cocoon shell weight, realized fecundity, shorter larval periods, and lower mortality than those fed on Scai diets ( Figure 1 ). Comparable estimates have been reported for life-history parameters of S. ricini reared on R. communis ( 36 , 53 55 ). The superior performance for various life-history traits in larvae fed Scr diets most probably reflects dietary habituation as a result of domestication on R. communis plants.…”
Section: Discussionsupporting
confidence: 55%
“…In this study, R. communis was a better host plant than A. excelsa , as S. ricini larvae fed on the Scr diet displayed significantly higher ( p ≤ 0.05) larval weight gain, cocoon shell weight, realized fecundity, shorter larval periods, and lower mortality than those fed on Scai diets ( Figure 1 ). Comparable estimates have been reported for life-history parameters of S. ricini reared on R. communis ( 36 , 53 55 ). The superior performance for various life-history traits in larvae fed Scr diets most probably reflects dietary habituation as a result of domestication on R. communis plants.…”
Section: Discussionsupporting
confidence: 55%
“…Temperature and humidity greatly affected the development of eggs. Our previous studies observed that eggs also developed in six days (Nurkomar et al 2022a(Nurkomar et al , 2022b. However, other studies reported that S. c. ricini eggs could develop in 8-9 days (Kavane 2014), ten days, and 14-15 days in the winter (Das and Das 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The refrigeration period will also not cause losses economically because there was no significant influence on the weight of the cocoon developed. The cocoons shell weighed the same as the weights of S. c. ricini cocoons reported in our previous studies (Nurkomar et al 2022b) and others (Tungjitwitayakul and Tatun 2017).…”
Section: Discussionmentioning
confidence: 98%
“…As C. picticeps ages, its chances of survival will decline. The kind of food consumed also has an impact on the survival rate as examined by other insects [7,8]. Brown eggs with an oval shape are laid solitary or do not form an egg mass.…”
Section: Resultsmentioning
confidence: 99%